2019
DOI: 10.1111/all.13790
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation dampens intestinal inflammation in a murine model of experimental food allergy

Abstract: Background The vagus nerve has emerged as an important modulator of the intestinal immune system. Its anti‐inflammatory properties have been previously shown in innate and Th1/Th17 predominant inflammatory models. To what extent the vagus nerve is of importance in Th2 inflammatory responses like food allergy is still unclear. In this study, we therefore aimed to investigate the effect of vagotomy (VGX) and vagus nerve stimulation (VNS), on the development and severity of experimental food allergy. Methods Balb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…However, anti-inflammatory neuro-immune modulation seems to involve different neuronal receptors in type 2-mediated intestinal disease models. For example, in a murine model of food allergy, VN stimulation ameliorated disease severity independently of α7nAChR 74 . Uptake of food antigens by anti-inflammatory CX3CR1 + MΦ and subsequent induction of food-specific Tregs effectively prevent allergic reactions 44 .…”
Section: Discussionmentioning
confidence: 99%
“…However, anti-inflammatory neuro-immune modulation seems to involve different neuronal receptors in type 2-mediated intestinal disease models. For example, in a murine model of food allergy, VN stimulation ameliorated disease severity independently of α7nAChR 74 . Uptake of food antigens by anti-inflammatory CX3CR1 + MΦ and subsequent induction of food-specific Tregs effectively prevent allergic reactions 44 .…”
Section: Discussionmentioning
confidence: 99%
“…VNS was indeed shown to exert an anti-inflammatory effect in a model of sepsis by modulation of macrophages via the α7 nicotinic acetylcholine receptor (α7nAChR). 4,5 Also in the gastrointestinal (GI) tract, we and others demonstrated that cervical VNS dampens macrophage activation in experimental colitis, 6,7 food allergy, 8 and postoperative ileus. 9,10 Interestingly, our group recently showed that electrical stimulation of both the subdiaphragmatic posterior and anterior vagal branches possesses similar anti-inflammatory properties as cervical VNS in mice 11,12 and thus could be used as an alternative approach for cervical VNS.…”
Section: Introductionmentioning
confidence: 92%
“…Vagotomy was shown to worsen inflammation in mouse models of colitis , independently of the α7 nicotinic acetylcholine receptors (α7nAChR) . On the contrary, vagus nerve stimulation (VNS) has been shown to improve local and systemic inflammation (i.e., reduced levels of inflammatory cytokines in the mucosa and serum) in mouse models of Th2 cells‐dependent colitis and food allergy . In addition, chronic electrical stimulation of the vagus nerve also ameliorated Trinitrobenzenesulfonic acid (TNBS)‐induced colitis in rats .…”
Section: Neural Detection and Regulation Of Bacteria‐associated Immunmentioning
confidence: 99%